Evaluasi Penerapan Konsep Ekowisata di Kampung Wisata Arborek, Raja Ampat - Novelina Tampubolon; Maria Mardia Marampa; Marjan Bato (Fakultas Perikanan dan Ilmu Kelautan, Universitas Papua, 2021)
Evaluation the application of the ecotourism concept in a tourist destination is considered important in maintaining the sustainability of tourism management. Arborek tourism village is one of the best tourist villages in Raja Ampat so that the selection as a research location is considered appropriate to evaluate the application of the ecotourism concept to every tourist activity so that the existence of Arborek Tourism Village is maintained. The purpose of this study is to evaluate the application of the ecotourism concept in the Arborek tourist village. The data was taken using a closed ended questionnaire and then analyzed using the One Score One Criteria Scoring System method. The results showed that tourism managers in Arborek Tourism Village had understood the concept of ecotourism; has a unique and distinctive characteristic, the existence of the carrying capacity of the community, government and has a selling value. It is the same with public perception which states that in terms of village conditions, the impact of tourism activities on the community and tourist facilities has an average score of 6 which means it is good. The same perception was expressed by tourists in terms of facilities and accessibility, namely a score of 6 (good) while for the tourist attraction aspect, tourists stated a score of 7 which means very good. In general, Arborek Tourism Village has implemented the concept of ecotourism well, however, to maintain the sustainability of tourism activities, cooperation between stakeholders involved (community, government and NGOs) is needed so that the sustainability of Arborek Tourism Village is maintained.